First human case report of sepsis due to infection with Streptococcus suis serotype 31 in Thailand. Issue 1 (December 2015) - Hatrongjit, Rujirat; Kerdsin, Anusak; Gottschalk, Marcelo; Takeuchi, Dan; Hamada, Shigeyuki; Oishi, Kazunori; Akeda, Yukihiro
Abstract Background Streptococcus suis is a zoonotic pathogen that causes invasive infections in humans and pigs. It has been reported thatS. suis infection in humans is mostly caused by serotype 2. However, human cases caused by other serotypes have rarely been reported. This is the first report of a human case of infection withS. suis serotype 31 in Thailand. Case presentation A 55-year-old male alcohol misuser with liver cirrhosis was admitted with sepsis to a hospital in the Central Region of Thailand. He had consumed a homemade, raw pork product prior to the onset of illness. He was alive after treatment with ceftriaxone and no complication occurred. An isolate from blood culture at the hospital was suspected as viridans groupStreptococcus . It was confirmed at a reference laboratory asS. suis serotype 31 by biochemical tests, 16S rDNA sequencing, and multiplex polymerase chain reaction for serotyping, but it was untypable by the co-agglutination test with antisera against recognizedS. suis serotypes, suggesting loss of capsular material. The absence of a capsule was confirmed by transmission electron microscopy. The isolate was confirmed to be sequence type 221, with 13 putative virulence genes that are usually found in serotype 2 strains. Conclusion We should be aware of the emergence ofS. suis infections caused by uncommon serotypes in patients with predisposing conditions. Laboratory capacity to identifyS. suis in the hospital is needed in developing countries, which can contribute to enhanced surveillance, epidemiological control, and prevention strategies in the prevalent area.